Regulation of the Right to Oblivion in Cyberspace: Heterogeneity of Loyalties in the Public Space for Postulation of Legitimate Interests - Allana Andery (GoAcademica Research & Publishing, 2021)
This article aims to broaden the understanding of the diversification of public responsibilities present in the intention of legislators to regulate the right to privacy and oblivion in Bill 7881/2014 and PLS 181/2014. The text adopts deductive reasoning, descriptive methodology combined with discourse analysis and theoretical framework in the General Theory of the State to explain the course of intervention that flows into the Regulatory State. The study identifies the international and economic inspiration of legislative proposals that aim to meet the demands of technological communication in a new market of data and information appropriation by corporations. The article strengthens the thesis of the diversification of public responsibilities and points out difficulties for the effectiveness of the proposed regulation due to the technical complexity and the asymmetry between users and research providers regarding the access and use of contents stored in the virtual world. The article points out contractual risks of the intense flow of exchanges on the internet and warns of the absence of a transnational State that will protect the right to privacy and oblivion globally, in the face of the power of large corporations.